Exploring the Effects of Bilingual Education Programs on English Language Development - Lesmana, Nadella (English Edu: Journal of English Teaching and Learning, 2024)
This study examines the impact of bilingual education programs on English language development among students from diverse linguistic backgrounds. Bilingual education programs use both the student's native language and English as mediums of instruction, aiming to develop bilingualism, biliteracy, and academic achievement. Key findings suggest that well-implemented bilingual programs contribute positively to English language development, with students achieving comparable or superior levels of proficiency compared to monolingual English-only programs. Bilingual education enhances metalinguistic awareness, facilitating the transfer of literacy skills from the native language to English, and provides cognitive benefits like improved executive function and problem-solving skills. It also fosters a more inclusive learning environment, enhancing students' self-esteem and motivation. Socio-cultural benefits, such as increased cultural awareness and sensitivity, promote a positive attitude towards learning English and other languages. However, the effectiveness of bilingual education programs depends on factors like program quality, teacher proficiency, and socio-political context. Future studies should explore best practices and address challenges to optimize the benefits of bilingual education.